Partitioning beta diversity of dry and hot valley vegetation in the Nujiang River in Southwest China - Zhao, Ziqing; He, Liping; Li, Guixiang; Ma, Saiyu; Cui, Ming; Liu, Yuguo; Chai, Yong (Frontiers in Ecology and Evolution, 2023)
The formation and continued maintenance of beta diversity are essential factors contributing to the effective conservation of plant community biodiversity and sustainable development of ecosystem functions. While it is widely acknowledged that two different patterns, including turnover and nestedness, strongly influence plant community beta diversity, their relative importance in the unique dry and hot valleys of Southwest China is yet to be fully understood. For this study, we established a 100km belt transect in the Nujiang dry and hot valley of Southwest China and conducted community investigations. The calculations of species and phylogenetic beta diversity composition patterns allowed us to explore the relative importance of environmental and dispersal limitations in terms of their contributions to beta diversity. The findings indicated that in the Nujiang dry and hot valley of Northwest Yunnan, species and phylogenetic beta diversity in the plant communities were mainly composed of the turnover component. The values of phylogenetic beta diversity and its turnover components were lower than those of species beta diversity. Both environmental and dispersal limitations played a role in partitioning beta diversity in the region, with environmental limitations being more dominant than dispersal limitations. The analysis of specific environmental factors revealed that climate factors, such as mean annual precipitation and Hargreaves reference evaporation, and soil factors, such as pH, were the primary drivers of species and phylogenetic beta diversity in the region. In addition, we observed that various limiting environmental factors related to the growth and development of different life forms existed within the dry and hot valley communities. The study highlighted the potential benefits of establishing conservation reserves featuring multiple dominant shrub species in the Nujiang dry and hot valley of Southwest China for the protection of the vegetation. The findings demonstrated that environmental factors, particularly hydrothermal conditions, played a significant role in constraining the maintenance of beta diversity in plant communities in the dry and hot valley region at a regional scale, given the geological history and environmental changes that have occurred over time.